How do you solve #-15( 2u + 6) = - 10( 3u + 15)#?

1 Answer
Sep 10, 2016

Answer:

#color(magenta)("IS THE QUESTION CORRECT?")#

Explanation:

Given:#" "-15(2u+6)=-10(3u+15)#

,~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

Multiply both sides by (-1)

#+15(2u+6)=+10(3u+15)#

Factor out the value 2 from the left hand brackets

#(15xx2(u+3)) =10(3u+15)#

#=>30(u+3)=10(3u+15)#

Factor out 3 from the right hand brackets

#=>30(u+3)=30(u+5)#

Divide both sides by 30

#=> u+3=u+5 color(red)(" This is a contradiction !")#

#color(magenta)("IS THE QUESTION CORRECT?")#